Kerjasama Guru dan Orang Tua dalam Menanamkan Akhlak Anak - Almira Dewi (Journal of Educational Research, 2022)
The purpose of this study is (1) to determine the cooperation between teachers and parents in instilling morals mahmudah in children, (2) to determine the indicators of factors inhibiting cooperation between teachers and parents in instilling morals mahmudah in children, (3) to determine what efforts have been made teachers and parents in building cooperation in instilling morals mahmudah in children. This study uses a qualitative descriptive approach with data collection conducted using observation, interview and documentation methods. The subjects were determined using purposive sample technique with data analysis technique using inductive descriptive analysis. Based on the data obtained by researchers on observations, it can be seen that the cooperation carried out by teachers and parents in planting morals mahmudah in Diniyyah Al-Azhar Jambi has been running smoothly, but during the pandemic activities that refer to the cultivation of morals mahmudah a little constrained because they cannot gather with many people. Tujuan dari penelitian ini antara lain; (1) untuk mengetahui kerjasama antara guru dan orang tua dalam menanaman akhlak mahmudah pada anak, (2) untuk mengetahui indikator faktor-faktor penghambat kerjasama guru dan orang tua dalam menanaman akhlak mahmudah pada anak, (3) untuk mengetahui upaya apa yang telah dilakukan guru dan orang tua dalam membangun kerjasama menanamkan akhlak mahmudah pada anak. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan pengumpulan data menggunakan metode observasi, wawancara dan dokumentasi. Subjek penelitian ditentukan menggunakan teknik purposive sample dengan teknik analisis data menggunakan analisis deskriptif bersifat induktif. Berdasarkan data yang sudah diperoleh peneliti pada pengamatan dapat diketahui bahwa kerjasama yang dilakukan oleh guru dan orang tua dalam penanaman akhlak mahmudah di Taman Kanak-Kanak Diniyyah Al-Azhar Kota Jambi sudah berjalan dengan lancar, akan tetapi selama pandemi kegiatan yang mengacu pada penanaman akhlak mahmudah sedikit terkendala dikarenakan tidak dapat berkumpul dengan banyak orang.